Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/brainsci11040504
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mechanical Thrombectomy using Penumbra ACETM Aspiration Catheter Compared to Stent Retriever SolitaireTM FR in Patients with Acute Ischemic Stroke

Abstract: Background: Mechanical thrombectomy is the standard therapy in patients with acute ischemic stroke (AIS). The primary aim of our study was to compare the procedural efficacy of the direct aspiration technique, using Penumbra ACETM aspiration catheter, and the stent retriever technique, with a SolitaireTM FR stent. Secondarily, we investigated treatment-dependent and treatment-independent factors that predict a good clinical outcome. Methods: We analyzed our series of mechanical thrombectomies using a Solitaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Stop pushing and confirm the cause of obstruction. Forced pushing may damage the device or vessels [ 13 ]. It is worth noting that after the stent is released, it should be kept in place for 5 minutes to open the occluded artery, which can quickly supply blood to the distal end and improve ischemic tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Stop pushing and confirm the cause of obstruction. Forced pushing may damage the device or vessels [ 13 ]. It is worth noting that after the stent is released, it should be kept in place for 5 minutes to open the occluded artery, which can quickly supply blood to the distal end and improve ischemic tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…In both KSOT and USOT groups, we identified the presentation of the pial arterial collateralization in the CT angiography scan at admission as the factor predicting a good clinical outcome. The presentation of the pial arterial collaterals on the CT angiography scan at admission in cases of successful vessel recanalization could be crucial for a good clinical outcome [24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…The penumbra pivotal stroke trial demonstrated safe use up to 8 h from stroke onset and an 82% recanalization rate in 125 patients [45]. This aspiration device shows similar clinical outcomes to the Solitaire FR stent retriever in a retrospective review of 76 patients [46]. However, it demonstrated higher rates of complete recanalization with lower device passage count, shorter procedure times, and shorter recanalization times [46][47][48][49][50].…”
Section: Aspiration Devicesmentioning
confidence: 99%
“…This aspiration device shows similar clinical outcomes to the Solitaire FR stent retriever in a retrospective review of 76 patients [ 46 ]. However, it demonstrated higher rates of complete recanalization with lower device passage count, shorter procedure times, and shorter recanalization times [ 46 - 50 ].…”
Section: Aspiration Devicesmentioning
confidence: 99%